The oiconymy of the Nadvelikoluzhzhya region - Ільченко, Iрина (Geographical names in physical space, 2016)
The article analyzes a lexical and semantic method of creation of oiconyms of Nadvelikoluzhzhya region. The structural classes of primary oyconyms are selected and presented according to their type, the routine dynamics of their development in reference to the naming of settlements.